2022
DOI: 10.3389/fpsyt.2022.1008124
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive analysis of endoplasmic reticulum stress and immune infiltration in major depressive disorder

Abstract: BackgroundMajor depressive disorder (MDD) is a life-threatening, debilitating mental health condition. An important factor in the development of depression is endoplasmic reticulum stress (ERS). However, their roles in MDD have not yet been established. The goal of this study was to examine ERS and its underlying molecular mechanisms in MDD.MethodsWe used data from two microarray datasets (GSE98793 and GSE39653) and the GeneCards database to examine the reticulum stress-related differentially expressed genes (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 91 publications
(106 reference statements)
1
4
0
Order By: Relevance
“…Inflammatory processes are specifically involved in MDD, and the immune profiles of MDD and control groups were analysed. The results revealed that the infiltration level of M0 macrophages was higher in MDD samples than in control samples, which was also observed by Zhang et al ( 51 ). A previous study indicated that a higher production of pro-inflammatory cytokines was detected in M0 macrophages in autologous sera from patients with MDD than in control samples ( 52 ).…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Inflammatory processes are specifically involved in MDD, and the immune profiles of MDD and control groups were analysed. The results revealed that the infiltration level of M0 macrophages was higher in MDD samples than in control samples, which was also observed by Zhang et al ( 51 ). A previous study indicated that a higher production of pro-inflammatory cytokines was detected in M0 macrophages in autologous sera from patients with MDD than in control samples ( 52 ).…”
Section: Discussionsupporting
confidence: 85%
“…The present analysis has some unique advantages. Compared with previous diagnostic model construction ( 51 ), our analysis employs a larger number of datasets and identifies two molecular subtypes associated with ERS, which may provide a more comprehensive understanding of MDD. Notably, our findings clarify several diagnostic signatures and molecular subtypes from the perspective of ERS, which can provide a deeper understanding of the molecular heterogeneity of depression; meanwhile, it is helpful to assist psychiatrists to formulate accurate and individualised treatment schemes, thus reducing the burden of depression.…”
Section: Discussionmentioning
confidence: 99%
“…Secondarily, the hsa05206 pathway, has been connected to the mechanism of action of saikogenin G, a bioactive ingredient of the traditional antidepressant treatment Radix Bupleuri in Chinese medicine [71], but has not been connected to response to lithium therapy in bipolar disorder [72]. b) hsa04621 pathway (includes CARD16 gene) implicates immunological deregulation in bipolar disorder [73], schizophrenia [74], [75] depression [76] and epilepsy [77] and is a target pathway for certain antiepileptics [78]. c) hsa04750 pathway (includes ASIC3 gene), has been connected to schizophrenia [79], post-stroke depression [80] and to metabolic syndrome in bipolar disorder and schizophrenia [81].…”
Section: Kegg Analysis Results and Neuropsychiatric Diseasementioning
confidence: 99%
“…hsa04621 pathway (includes CARD16 gene) implicates immunological deregulation in bipolar disorder [73], schizophrenia [74], [75] depression [76] and epilepsy [77] and is a target pathway for certain antiepileptics [78].…”
Section: Discussionmentioning
confidence: 99%
“…Psychiatric disorders like major depressive disorder (MDD), bipolar disorder (BD), and schizophrenia (SCZ) are associated with widespread molecular alterations in the brain, including alterations in neurotransmitter systems (serotonin, dopamine, norepinephrine, glutamate, GABA) (1-7), deficits in neuronal homeostasis (8,9), neuroinflammation (10)(11)(12), and oxidative and endoplasmic reticulum stress (13)(14)(15)(16)(17). They are also associated with brain circuit dysfunction at multiple scales, including large-scale brain networks like the default mode network (18,19), excitatory-inhibitory balance (20)(21)(22), and cortical microcircuits (23)(24)(25)(26)(27).…”
Section: Introductionmentioning
confidence: 99%